Respecting autonomy in severely demented patients through advanced medical directives - Li, Xue Er (2018)
This paper discusses the problem that Margo, a severely demented patient, faces when she has pneumonia. Pneumonia is easy to treat with the use of antibiotics, but if left untreated, it is lethal. The doctor has received her advanced medical directive (AMD), where she indicated that she would reject all forms of treatment that might prolong her life. Medical practitioners who are supposed to help patients face the dilemma between two principles of bioethics, namely the autonomy principle and the beneficence principle. I argue that Margo’s precedent autonomy, as expressed in the AMD should be respected despite her being pleasurably demented, where she seems to enjoy her current lifestyle. Failing to respect the AMD would mean to disrespect Margo as a person, even if there might be possible benefits when she gets the medication. Her AMD is an important tool, an expression of her autonomy, that allows her to extend her values and wishes to the future even when she is incompetent and it places constraints on what doctors can do to her body. It also helps Margo to continue to live her life as a coherent whole through a narrative that she has planned beforehand